PENGARUH TINGKAT AKURASI DALAM IDENTIFIKASI GEJALA DAN TANDA PENYAKIT PADA TANAMAN - Yasmine Mufidah; Richard Noah; Leady Lawalatta; Nuzul Bragas (P3M STMIK Profesional Makassar, 2022)
The development of technology in the industrial era 4.0 is now very advanced from year to year. Initially, only a small set of tools and simple machines in industries, then the development has become a modern orbit so that it can help to range from solving problems with human control to machines that can make their own decisions from the analysis they do. This called artificial intelligence. Specifically in the field of agriculture, artificial intelligence technology can be implemented to facilitate and even provide knowledge about technology for farmers and those working in agriculture. In this case, to see the effect of the level of accuracy in identifying symptoms and signs of disease in plants using the ResNet model architecture.